Immunohematological Outcome Among Adult HIV Patients Taking Highly Active Antiretroviral Therapy for at Least Six Months in Yabelo Hospital, Borana, Ethiopia - Ashenafi G; Tibebu M; Tilahun D; Tsegaye A (Journal of Blood Medicine, 2023)
Girma Ashenafi,1 Melatwork Tibebu,2 Dagnamyelew Tilahun,1 Aster Tsegaye2 1Department of Medical Laboratory Sciences, Bule Hora University, Bule Hora, Oromia, Ethiopia; 2Department of Medical Laboratory Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Melatwork Tibebu, Email melatwork.tibebu@aau.edu.etBackground: Immunohematological abnormalities among human immunodeficiency virus-infected patients are common abnormalities associated with severe depletion of the immune system, covering a stage of acute syndrome to an advanced disease. The greatest impact was observed in the low- and middle-income countries. However, in Ethiopia, little attention has been paid, and only limited published information exists regarding immunohematological abnormalities among individuals receiving highly active antiretroviral treatment.Objective: This study aimed to assess changes in immunological and hematological parameters in HIV-infected patients receiving HAART for at least six months at the antiretroviral therapy clinic of Yabelo Hospital, Borena, Ethiopia.Methods: A cross-sectional study was conducted from February to July 2021 using convenient sampling to recruit 333 participants. Sociodemographic data and clinical characteristics were collected using a pretested questionnaire. Baseline data were extracted from medical records and after six month immunohematological measurements were performed on blood samples collected during the study period. Data analysis was performed using SPSS version 25. Descriptive analysis was performed, and the results are presented as numbers and percentages or means ± SD. A paired t-test was used to compare the mean values of the immunohematological parameters before and after six of taking HAART. Statistical significance was set at P < 0.05.Results: The prevalence of anemia, leucopenia, neutropenia, lymphopenia and thrombocytopenia were 47.4%, 73.3%, 58.3%, 76.9% and 3.3% before initiation of HAART and 23.1%, 36.4%, 23.4%, 35.7% and 2.4% after initiation of HAART, respectively; Compared to baseline, there was also a significant decrease in the rate of Immunosuppression (CD4 < 350) from 62.2% at base line to 20.7% after HAART initiation.Conclusion: Immunohematological profile of the patients improved after the initiation of HAART. The observation of large proportion of immunosuppressed individuals at baseline warrants advocating for HIV testing in the pastoralist community so that infected patients could benefit from early initiation of HAART.Keywords: HIV, highly active antiretroviral therapy, immunohematological abnormalities